2021
DOI: 10.1016/j.metabol.2021.154726
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteomic analysis of IRS1 in skeletal muscle from men with normal glucose tolerance or type 2 diabetes: A case-control study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Indeed, we also found that the early upregulation of the activity read-out of IRS1 (Esposito et al , 2001), p-Irs1 Tyr608 , faded upon long exposure to IFN-β. Additionally, p-Irs1 Ser1134 and p-Irs1 Ser1137 displayed a biphasic trend, correlating with the activation status of mTOR (Copps & White, 2012; Karlsson et al , 2021; Langlais et al , 2011) (Appendix Table 1). This suggests that prolonged IFN-β exposure in NSCs induces negative feedback loops on Akt that ultimately inhibits mTORC1 (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we also found that the early upregulation of the activity read-out of IRS1 (Esposito et al , 2001), p-Irs1 Tyr608 , faded upon long exposure to IFN-β. Additionally, p-Irs1 Ser1134 and p-Irs1 Ser1137 displayed a biphasic trend, correlating with the activation status of mTOR (Copps & White, 2012; Karlsson et al , 2021; Langlais et al , 2011) (Appendix Table 1). This suggests that prolonged IFN-β exposure in NSCs induces negative feedback loops on Akt that ultimately inhibits mTORC1 (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
“…16 In clear contrast to adipose tissue, the phosphorylation of IRS1 in skeletal muscle was not uniformly altered in patients with type 2 diabetes, despite the severe insulin resistance in skeletal muscle, suggesting that the posttranscriptional modification of IRS1 differs between adipose tissue and skeletal muscle in type 2 diabetes. 17 ADAMTSL3, a member of the ADAMTS (a disintegrin and metalloprotease with thrombospondin motifs)-like subfamily, is a component of the extracellular matrix and is ubiquitously expressed, including in adipose tissue and skeletal muscle. 18 Genetic association studies have consistently shown that ADAMTSL3 polymorphisms are associated with adult height 19,20 and lean mass 9,12 in humans.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In clear contrast to adipose tissue, the phosphorylation of IRS1 in skeletal muscle was not uniformly altered in patients with type 2 diabetes, despite the severe insulin resistance in skeletal muscle, suggesting that the post‐transcriptional modification of IRS1 differs between adipose tissue and skeletal muscle in type 2 diabetes. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The iTRAQ strategy is similar to TMT. iTRAQ and TMT quantification strategies have been used to quantify tyrosine phosphorylation signaling networks with site‐specific resolution in different biological systems, such as EGF (Marzinke et al, 2013; Tzouros et al, 2013), insulin (Karlsson et al, 2021), T‐cell receptor (Estrada et al, 2021), and other tyrosine kinases (X. Wu, Wang, et al, 2021; Zhang et al, 2010). These two quantification strategies can provide more accurate quantitative information than stable isotope label‐free methods.…”
Section: Nontargeted Proteomics Analysis Of Tyrosine Phosphorylationmentioning
confidence: 99%